The Correlation Between Big Five Personality Types and the Level of Loneliness in Profession Nurse Students in the Agriculture Region - Erti Ikhtiarini Dewi; Ferdiana Sari Tidar; Yeni Fitria; Hanny Rasni; Enggal Hadi Kurniyawan (NurseLine Journal, 2023)
ABSTRACT Loneliness becomes a phenomenon in early adulthood due to the adolescent crisis towards early adulthood. One of the problems of loneliness is caused by a person's personality. Nursing students are prone to experiencing loneliness because they are in early adulthood, which at this age will go through a stage of psychological development, namely intimacy versus isolation. This study aims to determine the relationship between the big five personality types and the level of loneliness in nursing students. The research design used correlational quantitative with cross-sectional data collection. The number of samples used in this study was 95 respondents using a total sampling of students of the Nursing Professional Study Program, Faculty of Nursing, University of Jember. The Big Five Inventory (BFI) questionnaire was used to identify personality types, while the UCLA Loneliness Scale questionnaire was used to measure loneliness levels. It was found that 32 respondents (33.7%) had agreeableness personality types and 43 respondents (45.3%) experienced moderate loneliness. Data analysis was performed using the chi-square correlation test with a significance level of 0.05. The results showed a p-value of 0.649 indicating that there was no relationship between the big five personality types and loneliness in college students. This happens because it is influenced by several factors such as where you live, the presence of close friends and someone special who will provide space for someone to interact so that feelings of loneliness are reduced. Keywords: Big Five Personality; Loneliness; Nursing Students.